Unexpected Delayed Colon Perforation after the Endoscopic Submucosal Dissection with Snaring of a Laterally Spreading Tumor - Young Bo Ko; Jeong-Mi Lee; Wan Soo Kim; Min Seob Kwak; Ji Wan Lee; Dong Yeol Shin; Dong-Hoon Yang; Jeong-Sik Byeon (Korean Society of Gastrointestinal Endoscopy, 2015)
Colonic perforation may occur as a complication of diagnostic and therapeutic colonoscopy. The risk factors for perforation after colorectal endoscopic submucosal dissection (ESD) include an inexperienced endoscopist, a large tumor size, and submucosal fibrosis. The mechanisms of perforation include unintended endoscopic resection/dissection and severe thermal injury. Here, we report a case of colon perforation that occurred after ESD with snaring of a laterally spreading tumor. The perforation was completely unexpected because there were no colorectal ESD-associated risk factors for perforation, deep dissection, or severe coagulation injury in our patient.